DIFFERENCES IN CHANGES OF HEMOGLOBIN BETWEEN 6-12 HOURS AND 12-14 HOURS AFTER TRANSFUSION - Rosita Linda; Devita Ninda (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Each year more than 41,000 blood donations are needed every day and 30 million blood components are transfused. Blood products that can be transfused include Packed Red Cells (PRC), Whole Blood (WB), Thrombocyte Concentrate (TC), Fresh Frozen Plasma (FFP). Monitoring Hemoglobin (Hb) after transfusion is essential for assessing the success of a transfusion. The time factor after transfusion for Hemoglobin (Hb) examination needs to be established, analyze to judge the success of a blood transfusion which is performed. The aim of this study was to analyze the differences in changes of hemoglobin between 6-12 hours, and 12-24 hours after-transfusion. This study was retrospective observational using secondary data. The subjects were patients who received PRC, and WBC transfusion. At 6-12, and 12-24 hours after-transfusion, hemoglobin, RBC, and hematocrit were measured. Then the data were analyzed by unpaired t-test. The collected data included the results of the Hb pre-transfusion, 6-12, and 12-24 hours after-transfusion. The subjects of this study were 98 people. The administration of transfusion increased by 10-30% in hemoglobin concentration at 6-12 hours after-transfusion. While at 12-24 hours after-transfusion, hemoglobin after-transfusion increased 15-37% from the baseline. Hemoglobin values were not different at any of the defined after-transfusion times (p = 0.76 (p>0.05)). Hemoglobin values were not different at 6-12 hours, and 12-24 hours after-transfusion. Keywords: Hemoglobin, measurement, after-transfusion